High-performance browser networking - Grigorik, Ilya (Beijing [et all.] : O'Reilly, 2013)
Highlights innovations for building even more powerful browser apps including HTTP 2.0, XHR improvements, Server-Sent Events (SSEs), WebSocket, and WebRTC.
Networking 101 -- Performance of wireless networks -- HTTP -- Browser APIs and protocols.
"What every web developer should know about networking and browser performance."--Cover.
Includes index.
Keywords: Computer networks